2003
DOI: 10.1136/adc.88.9.812
|View full text |Cite
|
Sign up to set email alerts
|

Radiological and biochemical resolution of nutritional rickets with calcium * COMMENTARY

Abstract: Aims: To determine the response to oral calcium in Nigerian children with rickets. Methods: In a teaching hospital in Western Nigeria, 26 children (13 boys, 13 girls, aged 2-5 years) with confirmed rickets received calcium lactate (2.7 g/day). Results: Within one month of treatment leg pain was relieved and the children were more active. The mean x ray score improved from 3.3 at baseline to 1.7 at three months and 0.9 at six months (arbitrary scoring system, 0-6). Twelve cases were healed radiologically after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 35 publications
4
36
0
Order By: Relevance
“…Like in our study, tribe and religion were not found to be significant factors as children with rickets have been reported among all Nigerian tribes in among both Christians and Moslems (Oginni et al, 2003;Graff et al, 2004). Older respondents (>50 years old) were less aware of children with knee deformity as compared to women in the active childbearing age group.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Like in our study, tribe and religion were not found to be significant factors as children with rickets have been reported among all Nigerian tribes in among both Christians and Moslems (Oginni et al, 2003;Graff et al, 2004). Older respondents (>50 years old) were less aware of children with knee deformity as compared to women in the active childbearing age group.…”
Section: Discussionmentioning
confidence: 43%
“…A figure of 2.4% for overt rickets and 15% for suggestive rickets has been reported from Maiduguri, Nigeria (Akpede et al, 1999). In furtherance to the rickets as a major health problem, Oginni et al (2003) have reported a frequency of 1-2 active rickets per week presenting to the Wesley Guilds Hospital at the Ilesa Unit of the Obafemi Awolowo University Teaching Hospital Complex in Ile Ife, Nigeria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process is nicely illustrated in cases of childhood rickets and osteomalacia where poorly mineralized bone is associated with markedly elevated circulating BALP levels that decrease during bone healing [5,6]. Additional information on the mineralization state of bone in patients with type 2 diabetes mellitus has been provided by bone histomorphometric indices that demonstrate significantly reduced amount of mineralizing surface and lower bone formation rate in comparison with age-matched non-diabetic controls (Figure) [7].…”
Section: Dear Editormentioning
confidence: 97%
“…[1][2][3][4] Nutritional rickets has been widely studied in terms of aetiologies, 3,4 variants, [5][6][7] clinical presentations, 8,9 and drug treatments [10][11][12] and responses. 13,14 The growth plates of the proximal femur develop rapidly during infancy and childhood. 15 Traditional methods to study development of the proximal femur involve cadaveric dissection, 16 experiments in animals, 17 radiography, and magnetic resonance imaging.…”
Section: Introductionmentioning
confidence: 99%